Alteration of food consumption and body mass of whey proteins supplemented rats - Marcos Roberto Campos de Macêdo; Antonio Coppi Navarro; Raphael Furtado Marques; Melaine Mont´Alverne Lawall Silva; Flavia Castello Branco Vidal; Alanna Joselle Santiago Silva; Carlos Eduardo Neves Amorim; Francisco Navarro (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2023)
Introduction: Whey proteins have received great attention because of their benefits on skeletal muscle hypertrophy, body fat reduction, performance, appetite regulation, immune system regulation, regulation of the lipid profile and the combat against metabolic stress. In this sense, their importance is often overestimated, leading athletes and physical activity individuals to consume very high doses of protein, without the guarantee of additional benefits.  Aim: For 12 weeks quantify the evolution of food intake and total body mass of Wistar rats supplemented with whey proteins with dosages of 2, 4, 6g/kg/day. Materials and methods: Approval protocol of the Ethics Committee on the Use of Animals of the Federal University of Maranhão nº 23115.014424 / 2015-54). An experimental research design was adopted with the rats being randomly distributed in 4 groups: Control Group (C), Supplemented groups (W2, W4, W6); the study was performed with 38 male Rattus novergicus Wistar rats with initial age of 60 days and body mass between 218 and 323 grams; supplementation with whey proteins dissolved in water followed the dosages 2, 4 and 6 g / kg / day supplementation was performed for 12 weeks, daily, three times a day, by volume of 5 ml, with an hour interval between each gavage. Variables were tested for distribution using the Shapiro-Wilk test (P> 0.05). The data of the feed consumption were analyzed by the ANOVA test; the classification variable was the interaction between feed consumption or body mass and supplementation (C, W2, W4, W6); the Tukey post-test was used to determine the statistical differences between the groups (C, W2, W4, W6), GraphPad Prism 7 software was used. Results: The mean intake of rations in the control group did not present a statistically significant difference in relation to the Whey 4 group at weeks 1 (p=0,3450), 2 (p=0,1027), 3 (p=0,1595), 4 (p=0,5572) and 5 (p=0,2539). There was a statistically significant difference in the increase of the total body mass of the control group compared to the Whey 4 group at weeks 10 (p=0,0454), 12 (p=0,0348) and at the final week (p=0,0138). Likewise, there was a significant statistical difference in the increase of the total body mass of the control group compared to the Whey group 6 in the final week (p=0,0048). In the same sense, there was a statistically significant difference in the total body mass increase of the Whey 2 group compared to the Whey 6 group in weeks 1 (p=0,0210), 2 (p=0,0434) and in the final week (p=0,0289). Discussion: Diets with high protein content play an important role in satiety due to its involvement with intestinal production of several anorectic hormones, which in turn stimulate the vagus nerve, promoting neuronal stimuli to the solitary tract nucleus, signaling satiety. As a result, the long-term ingestion of a high-protein diet reduces not only food intake, but also body mass and body adiposity in rats. Conclusion: Supplementation with serum whey proteins at doses of 4 and 6 g/kg/day in sedentary animals conferred stability over total body weight and a significant reduction in feed intake over 12 weeks. Supplementation with serum whey proteins at 2 g/kg/day in sedentary animals did not lead to a reduction in the average feed intake and showed a similar effect to the other doses on total body weight.